Why and How to Paraphrase - Salim, Hashim Saadoon; Al-Dulaimy, Ali Sulaiman I. (جامعة تكريت - كلية الآداب, 2019)
Specialists in the field of paraphrasing assure that awkward paraphrases often raise problems for readers and listeners in understanding what has been written or said in the original text. Such problems emerge when the paraphraser fails to convey the exact meaning of the source text. Anyhow, bad paraphrasing changes and damages the real meaning of the source text. Any increase or decrease in paraphrasing will affect negatively the meaning of the main text. In other words, bad paraphrasing affects negatively the receptor who can easily see the semantic differences between the paraphrased text and the source one. The procedure to be followed in this paper is presentation of the available literature relative to the subject of paraphrasing. The researchers have put their own views and comments on the subject. Besides, the available literature which has strong relationship to paraphrasing, such as plagiarism, note-taking, summary making etc. is presented with conclusions arrived at listed by the end of this study. This study is anticipated to be of use to researchers, scholars, teachers of English, i.e., the significance of this paper is clearly manifested in its advantage for teachers and researchers for pedagogical purposes in their instructional duties. The researchers of this paper, however, believe that the subject of paraphrasing is a significant one which deserves the effort exerted on it. The aim of this study is to supply the reader with a convenient and detailed insight into the subject "paraphrasing" with relative topics mentioned previously and to offer solutions to the difficulties which face the scholars and the researchers.
Keywords: التلخيص -- الاقتباس -- إعادة الصياغة -- البحوث العلمية